Internal communication in a diverse and developing world context: Challenges for corporate South Africa - Lucinda Bella-May Sutton; Tanya le Roux; Lynnette M Fourie (Communicare)
Internal communication plays a pivotal part in an organisation’s survival. It is regarded as an investment in an organisation’s success and underpins organisational effectiveness. However, when organisations face internal communication challenges, these can threaten internal relationships, with dire consequences for the organisation. This is particularly so in the volatile, uncertain, complicated and ambiguous South African corporate context, which presents direct challenges for internal communication management.